Academic and professional discourse genres in Spanish - Parodi, Giovanni (Studies in corpus linguistics ;, 2010)
This volume offers a description and a deep examination of discourse genres across four disciplines (Psychology, Social Work, Industrial Chemistry, and Construction Engineering), in academic and professional settings. The study is based on one of the largest available corpus on disciplinary written discourse in Spanish (PUCV-2006 Corpus of Spanish containing almost 60 million words). Twelve chapters range from the theoretical guiding principles of the research in terms of genre conception, the detailed description of each corpus (academic and professional), computational analysis from multi-d.